The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3109/02770903.2010.485665
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Pilot Study of Acupuncture as an Adjunct Therapy in Adult Asthmatic Patients

Abstract: Acupuncture as an adjunct therapy to conventional medical care does not seem to affect pulmonary function in asthmatic patients. However, 12 sessions of acupuncture treatment during 4 weeks showed a favorable effect on the quality of life in adult asthmatic patients. Further large trials assessing the effectiveness of acupuncture on the quality of life and symptoms in asthmatic patients are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…Symptomatic treatment includes oxygen and opioids although there may be side effects of both therapies. Past literature include a number of studies assessing acupuncture for cancer-related fatigue [25] as well as studies in patients with chronic obstructive pulmonary disease and asthma that demonstrate the effectiveness of acupuncture for fatigue and dyspnea symptom management [26,27].…”
Section: Cancer Fatiguementioning
confidence: 99%
“…Symptomatic treatment includes oxygen and opioids although there may be side effects of both therapies. Past literature include a number of studies assessing acupuncture for cancer-related fatigue [25] as well as studies in patients with chronic obstructive pulmonary disease and asthma that demonstrate the effectiveness of acupuncture for fatigue and dyspnea symptom management [26,27].…”
Section: Cancer Fatiguementioning
confidence: 99%
“…Use does not differ by race or ethnicity 114. Slader’s review found that few studies have shown efficacy in asthma, and therefore conclusions are of limited use due to inadequate quality and small sample sizes 113,115121. At least one study reported adverse effects of use of herbal products for asthma management 122.…”
Section: Resultsmentioning
confidence: 99%
“…While there was some signal that patient-centered outcomes such as QOL, nonpathophysiologic measures were improved, this technique is unlikely to reduce the need for pharmacologic therapies,119 though one study found promising results 120. The guidelines state that there is insufficient evidence to recommend/not recommend CAM, with two exceptions: acupuncture is contraindicated in the treatment of asthma (a recent study in 2010 also found no improvement in pulmonary function, though there was a “favorable effect” on QOL),121 and certain herbal preparations are cautioned against for risk of potential harm secondary to either interactions with recommended asthma medications and/or they may be irritants. Most importantly, since up to half of patients do not report CAM use to their clinicians,122 the guidelines recommend that clinicians specifically inquire about their patients’ use of CAM and advise against substituting CAM for their clinicians’ recommended treatment plan.…”
Section: Resultsmentioning
confidence: 99%
“…However, it remains unclear whether the use of CAM would have beneficial or adverse outcomes for benign or malignant diseases. Epidemiological studies have reported that pharmacopuncture has significant beneficial effects for subjects with asthma compared to conventional treatment 17 but there are no clear positive effects of CAM use in the control of asthma 18,19 . Clinical significance of CAM use in subjects with malignancy is relatively minimal 20 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Epidemiological studies have reported that pharmacopuncture has significant beneficial effects for subjects with asthma compared to conventional treatment 17 but there are no clear positive effects of CAM use in the control of asthma. 18,19 Clinical significance of CAM use in subjects with malignancy is relatively minimal. 20 CAM also represents an additional treatment modality for patients with ARDs including malignant mesothelioma who have limited treatment options.…”
Section: What Is Known and Objectivementioning
confidence: 99%